Na+/K+-ATPase Alpha 2 Isoform Elicits Rac1-Dependent Oxidative Stress and TLR4-Induced Inflammation in the Hypothalamic Paraventricular Nucleus in High Salt-Induced Hypertension - Qing Su; Xiao-Jing Yu; Xiao-Min Wang; Bo Peng; Juan Bai; Hong-Bao Li; Ying Li; Wen-Jie Xia; Li-Yan Fu; Kai-Li Liu; Jin-Jun Liu; Yu-Ming Kang (MDPI AG, 2022)
Background: Numerous studies have indicated that a high salt diet inhibits brain Na+/K+-ATPase (NKA) activity, and affects oxidative stress and inflammation in the paraventricular nucleus (PVN). Furthermore, Na+/K+-ATPase alpha 2-isoform (NKA α2) may be a target in the brain, taking part in the development of salt-dependent hypertension. Therefore, we hypothesized that NKA α2 regulates oxidative stress and inflammation in the PVN in the context of salt-induced hypertension. Methods: Part I: We assessed NKA subunits (NKA α1, NKA α2, and NKA α3), Na+/K+-ATPase activity, oxidative stress, and inflammation in a high salt group (8% NaCl) and normal salt group (0.3% NaCl). Part II: NKA α2 short hairpin RNA (shRNA) was bilaterally microinjected into the PVN of salt-induced hypertensive rats to knockdown NKA α2, and we explored whether NKA α2 regulates downstream signaling pathways related to protein kinase C γ (PKC γ)-dependent oxidative stress and toll-like receptor 4 (TLR4)-induced inflammation in the PVN to promote the development of hypertension. Results: High salt diet increased NKA α1 and NKA α2 protein expression in the PVN but had no effect on NKA α3 compared to the normal salt diet. Na+/K+-ATPase activity and ADP/ATP ratio was lower, but NAD(P)H activity and NF-κB activity in the PVN were higher after a high salt diet. Bilateral PVN microinjection of NKA α2 shRNA not only improved Na+/K+-ATPase activity and ADP/ATP ratio but also suppressed PKC γ-dependent oxidative stress and TLR4-dependent inflammation in the PVN, thus decreasing sympathetic activity in rats with salt-induced hypertension. Conclusions: NKA α2 in the PVN elicits PKC γ/Rac1/NAD (P)H-dependent oxidative stress and TLR4/MyD88/NF-κB-induced inflammation in the PVN, thus increasing MAP and sympathetic activity during the development of salt-induced hypertension.